Design of a 500w Inverter. - Kyomuhendo Medius (Kabale University, 2023)
An inverter is an electrical device that converts direct current (DC) to alternating current (AC). The converted AC can be at any required voltage and frequency with the use of appropriate transformers, switching and control circuits. An inverter is essentially the opposite of a rectifier. In this project work, a 500W power inverter system was designed, simulated and constructed. The values of the various components were determined before the simulations were embarked upon using electronic workbench: Multisim software. The inverter circuit in this project work is based on the operation of the oscillator. 12V AC is stepped up to 240V AC by using a step-up transformer. The assembled composite unit worked well. The oscilloscope measurement tallied with the set frequency of 50Hz and the square wave oscillator output. The inverter system is capable of providing power to the appropriate load for up to eight hours; depending on the state of the 12V batteries. KEYWORDS: Inverter, electricity generation, Multisim, square wave, Proteus